Incidente de resolução de demandas repetitivas - Temer, Sofia Orberg (2019)
This academic work analyses the incidente de resolução de demandas repetitivas (IRDR), or incident for decision about repetitive claims , introduced in the Brazilian Civil Procedure Code of 2015. It is a procedural instrument destined to solve common issues repeated in several claims, generating risk of violating equality and juridical safety. This proceeding aims to establish a juridical thesis applicable to all claims. The intent of this study is to present a systemization of such proceeding, approaching the contexts and motives for is set up, its object, nature, and processing. In addition to analyzing the procedural stages of the incident, from its filing up to the application of the thesis, this work emphasizes the analysis and systemization of the subjective structure of the incident, aiming at delimiting the engagement possibilities of individuals upon construction of the decision that deems merit of the IRDR. This work also focuses on the analysis of the decision that establishes the juridical thesis applicable to the repetitive claims, analyzing their elements and efficacy. The aim of this study is to present certain elements to set up an adequate dogmatic for such procedural technique